2004
DOI: 10.1897/02-632
|View full text |Cite
|
Sign up to set email alerts
|

Bioluminescence inhibition assays for toxicity screening of wood extractives and biocides in paper mill process waters

Abstract: The risk associated with wood extractives, biocides, and other additives in pulp and paper mill effluents was evaluated by performing a characterization of process waters and effluents in terms of toxicity and chemical analysis. The individual toxicity of 10 resin acids, two unsaturated fatty acids, and three biocides was estimated by measuring the bioluminescence inhibition with a ToxAlert 100 system. Median effective concentration values (EC50) of 4.3 to 17.9, 1.2 to 1.5, and 0.022 to 0.50 mg/L were obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 37 publications
1
32
0
Order By: Relevance
“…Resin acids are very resistant to chemical degradation due to their stable tricyclic structure (Dethlefs and Stan 1996). They are thought to be the main contributors to the toxicity of the pulp mill effluents (Makris and Banerjee 2002;Rigol et al 2004) and have been reported to end up in sediments of the receiving water bodies (Dethlefs and Stan 1996;Rämänen et al 2010). In addition to substances originating in the wood, there may be situations in which P&P wastewater contains toxins from other sources.…”
Section: Non-chlorinated Recalcitrant Compoundsmentioning
confidence: 99%
“…Resin acids are very resistant to chemical degradation due to their stable tricyclic structure (Dethlefs and Stan 1996). They are thought to be the main contributors to the toxicity of the pulp mill effluents (Makris and Banerjee 2002;Rigol et al 2004) and have been reported to end up in sediments of the receiving water bodies (Dethlefs and Stan 1996;Rämänen et al 2010). In addition to substances originating in the wood, there may be situations in which P&P wastewater contains toxins from other sources.…”
Section: Non-chlorinated Recalcitrant Compoundsmentioning
confidence: 99%
“…As such, it is of concern because of its detrimental effects on fish, including liver dysfunction, hemolysis of red blood cells, organ and tissue lesions, and genotoxic and neurotoxic effects (Zheng and Nicholson, 1998;Rabergh et al, 1999;Pacheco and Santos, 2002;Teles et al, 2004). It seems to be less toxic than most other resin acids (Peng and Roberts, 2000;Rigol et al, 2004). Beier et al (2000) summarize the biological effects of this compound.…”
Section: Insecticidal Activitymentioning
confidence: 99%
“…IC T and IT T are luminescence values for control and test samples measured after FT_ minutes exposure time and KF is the correction factor based on the control/ blank. Various researchers have used variable exposure time, e.g., 5 min (DeZwart and Sloof, 1983), 15 min (Rigol et al, 2004), and 30 min (Loibner et al, 2004). The concentration of the toxicant (mg/L) which caused a 50% reduction in light after exposure for FT_ minutes is designated as the EC 50 .…”
Section: Test Procedures and Its Variationsmentioning
confidence: 99%
“…It has been used for measuring short and long-term photoinduced toxicity of polynuclear aromatic hydrocarbons (PAHs) (El-Alawi et al, 2002). Bioluminescence inhibition assay has been applied as a sensitive and rapid screening tool for determining the whole effluent toxicity for various industrial effluents, i.e., dye wastewater from textile industry (Davere and Bahadir, 1994); and whitewater and effluent from paper mill (Rigol et al, 2004). Salizzato et al (1998) successfully applied the solid phase assay to lagoon sediments (< 63 Am) using a modified protocol for correlating the toxic units (TU = 100/EC 50 ) for sediments obtained from a lagoon to the composition of organic and inorganic toxicants.…”
Section: Applications Of Bioluminescence Inhibition Assaymentioning
confidence: 99%